COMPARATIVE ANALYSIS OF FINANSIAL PERFORMANCE IN ISLAMIC BANKS: A CASE STUDY OF INDONESIA AND MALAYSIA USING SHARIA CONFORMITY AND PROFITABILITY (2018 – 2024) - Kusmanningrum, Yunita; Maknuun, Lu’lu’il; Masuwd, Mowafg Abrahem (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: This study aims to compare the financial performance of Islamic commercial banks in Indonesia and Malaysia using the Sharia Conformity and Profitability (SCnP) framework, focusing on their alignment with sharia principles and profitability levels. Design/Methodology/Approach: A quantitative descriptive method was used, with secondary data obtained from Islamic bank financial reports and official sources such as OJK, IFSB, and PSIFIs. The SCnP model served as the primary analytical tool, and all Islamic commercial banks in both countries were included using saturated sampling. Research findings: Islamic banks in Indonesia showed fluctuating yet improving financial performance, particularly in profitability, reaching optimal position in 2024. However, challenges remain in maintaining consistent sharia compliance. Malaysian Islamic banks, meanwhile, consistently occupied the upper-left quadrant (ULQ), indicating strong profitability but limited use of profit-sharing instruments. Theoretical Contribution/Originality: This study contributes to the literature by applying the SCnP model in a cross-country comparison, highlighting the influence of regulatory systems and governance on Islamic banking performance. Practitioners/Policy Implications: Findings suggest that Indonesian banks should improve governance and investment screening, while Malaysian banks may benefit from enhancing the adoption of profit-sharing contracts to align more closely with Islamic ethical objectives. Research Limitations/Implications:The study is limited to quantitative data and excludes qualitative aspects such as governance and customer perception. Future research is encouraged to integrate these dimensions for a more comprehensive evaluation.